Firm-embedded productivity and cross-country income differences - Vanessa Alviarez; Javier Cravino; Natalia Ramondo (Inter-American Development Bank (IDB), 2021)
We measure the contribution of firm-embedded productivity to cross-country income differences. By firm-embedded productivity we refer to the components of productivity that differ across firms and that can be transferred internationally, such as blueprints, management practices, and intangible capital. Our approach relies on micro-level data on the cross-border operations of multinational enterprises (MNEs). We compare the market shares of the exact same MNE in different countries and document that they are about four times larger in developing than in high-income coun-tries. This finding indicates that MNEs face less competition in less-developed coun-tries, suggesting that firm-embedded productivity in those countries is scarce. We propose and implement a new measure of firm-embedded productivity based on this observation. We find a strong positive correlation between our measure and output per worker across countries. In our sample, differences in firm-embedded productivity account for roughly a third of the cross-country variance in output per worker.
Keywords: O4; O1; F41; F23; F62; 330; Development Accounting; TFP; Multinational Enterprises